Analytical model of large-diameter viscoelastic floating pile and application in pile low-strain integrity testing. Issue 158 (July 2022) - Meng, Kun; Su, Huifeng
Abstract: Based on a three-dimensional fictitious soil pile model, a rigorous analytical model of a large-diameter viscoelastic floating pile is developed by considering the material damping of the pile and the soil. Subsequently, closed-form solutions of the pile dynamic response of this analytical problem are derived. The rationality and accuracy of the proposed model and its relevant theoretical solutions are verified by comparison with the results of previous studies. Finally, parametric analyses are further conducted to investigate the effects of the radial direction position, length of the fictitious soil pile, material damping coefficient of the pile, and soil-to-pile stiffness ratios on the dynamic response of the pile. Based on the obtained results, an appropriate method to eliminate high-frequency interferences and evaluate the material damping coefficient of a pile in actual pile low-strain integrity testing is established. Furthermore, the proposed methodology affords legible theoretical insights into the wave propagation in large-diameter viscoelastic floating piles. Highlights: A rigorous mathematical model of a large-diameter viscoelastic floating pile is developed. The present methodology can be used to eliminate the high-frequency interferences in pile integrity testing. A method to evaluate the material damping coefficient of piles is established. The proposed method provides theoretical insights on the wave propagation in large-diameter viscoelastic floating piles.